Metabolic dysfunction-associated fatty liver disease and cardiovascular disease: A meta-analysis - Wen, Wen; Li, Hong; Wang, Chunyi; Chen, Chen; Tang, Jiake; Zhou, Mengyun; Hong, Xuwei; Cheng, Yongran; Wu, Qi; Zhang, Xingwei; Feng, Zhanhui; Wang, Mingwei (Frontiers in Endocrinology, 2022)
Background: Metabolic dysfunction–associated fatty liver disease (MAFLD, formerly known as nonalcoholic fatty liver disease, NAFLD) is one of the most important causes of liver disease worldwide, while cardiovascular disease (CVD) is still one of the main causes of morbidity and mortality worldwide, and the two are closely related. This study aimed to investigate the risk of CVD incidence or CVD–related mortality (CVD mortality) in patients diagnosed with MAFLD under new concepts and new diagnostic criteria. Methods: We searched English databases PubMed, Web of Science, Embase, and Cochrane Library for relevant literature. The language was restricted to English. Results: By January 22, 2022, 556 published studies were obtained through preliminary retrieval, and 10 cohort studies were included in this study. All statistical analyses were performed using Review Manager 5.2 software. Compared with the control group, patients in the MAFLD group had a significantly higher relative risk of CVD incidence or CVD mortality during the follow-up, with an RR rate of 1.95 (95% CI 1.76–2.17, P< 0.01). The incidence of CVD in the MAFLD group was more than twice that in the control group (RR 2.26, 95% CI 2.00–2.54, P< 0.01). The mortality rate of CVD was 1.57 times higher than that in the control group (RR 1.57, 95% CI 1.42–1.72, P< 0.01). Conclusions: Patients diagnosed with MAFLD alone had higher cardiovascular mortality than those diagnosed with NAFLD alone based on the available data.